The innovation position of four neighbouring countries and Hungary Based on the "European Innovation Scoreboard" - Sitányi, László (REGIONAL AND BUSINESS STUDIES, 2010)
As we know innovation systems can be distinguished not only at national, but also at global or regional levels, and even in the local networks, industrial corporation groups and clusters of firms. Still, the system needs to be examined at a national level as well, because the national attributes from a given country’s viewpoint may have an influence on the development of other levels (Pap and Sitányi, 2007). Although the global-local economic and social processes – taking effect in parallel – resulted in the weakening of the national level in the past two decades, Lundvall (1988) still deems their further analysis important because of the role of the common language and common culture. The author of this article attempts to draw the relative innovation path of the five neighbouring countries of In-Between Europe and also to demonstrate their position on the relative European innovation basis. For this the author has studied the European Innovation Scoreboard, EIS – established at the initiative of the European Union under the Lisbon Strategy – year by year. The comparative method defined and demonstrated in the article in full details can be applied to the demonstration of the relative position of any European blocks of countries or others outside Europe.